A study on the factors influencing the turnover of knowledge employees in state-owned enterprises: taking CZ company as a case - Yunhong Xu; Rini Suryati Sulong; Xuming Wu (Atlantis Press, 2023)
Under the background of knowledge economy, the competition among enterprises is gradually condensed into that for human resources. However, the turnover rate of employee in stated-owned enterprises is actually getting higher and higher, particularly, the knowledge staff. CZ Company is chosen as a case to examine the factors influencing knowledge employee turnover in stated-owned enterprises. After data analysis, it is found that promotional opportunity, job stress, distributive justice, autonomy have a significant positive impact on employee turnover. Some suggestions are proposed to decrease the employee turnover in stated-owned enterprises in this paper.